Multi-criteria method for supporting decisions on selecting water pipes for renovation or replacement - Rożnowski, Mateusz; Szpak, Dawid; Żywiec, Jakub; Tchórzewska-Cieślak, Barbara (Instal, 2026)
Public water supply systems are designed to provide consumers with a continuous supply of water at the right pressure and quality. In order to fulfil these tasks, the water supply network must be constantly monitored and modernised. Due to limited investment funds, water supply companies must carefully select pipes whose technical condition and/or improper operation may lead to failures and interruptions in water supply to consumers. The paper presents a multi-criteria decision support method called FSAW (Fuzzy Simple Additive Weighting Method). The method was used to select water pipes that should be replaced or renovated first. The presented proprietary decision-making criteria and decision parameter values are an important tool for taking action in the analysed issue. A case study was developed for 9 variants of water pipes. Based on the analysis, the order of renovation or replacement of the tested water pipes was determined. An additional result of the work is the development of calculation formulas for use in the QGIS programme and the visualisation of the research results on a digital map of the water supply network.
Keywords: FSAW; replacement of water pipes; decision support